A Brief History of Gender Law Journals: The Heritage of Myra Bradwell’s Chicago Legal News - Chused, Richard H. (Columbia Journal of Gender and Law, 2003)
In the front of the first issue of the Columbia Journal of Gender and Law published twelve years ago, the members of the staff inserted a brief statement of purpose. Claiming that their “working job titles confer[red] no greater or lesser power, but serve[d] only to define primary responsibilities,” they hoped “to publish legal and interdisciplinary writings on feminism and gender issues and to expand feminist jurisprudence., For its moment in history, this was a fairly radical statement of purpose. Eschewing most aspects of hierarchy and viewing their primary audience as students and academics, the members aimed “to promote an expansive view of feminism embracing women and men of different colors, classes, sexual orientations, and cultures. A brief comment by Ruth Bader Ginsburg followed immediately after the journal members’ statement of purpose. She focused not on theoretical and philosophical questions, but on events preceding her rise to a position of power and authority. Harking back to the lament of a 1922 Barnard graduate who was denied admission to Columbia Law School, recalling the faculty decision to reverse that result and accept women as students in 1928, recollecting (with a certain perverse glee I am sure) that Harvard declined to accept women until 1950, and recognizing the enormous legal and cultural changes of the 1970s, Justice Ginsburg dwelled on the sorts of practical steps taken by courageous women and men to alter the landscape of the legal academy and the legal profession.